1990
DOI: 10.1111/j.1751-1097.1990.tb01811.x
|View full text |Cite
|
Sign up to set email alerts
|

SINGLE‐ and DOUBLE‐STRAND BREAK FORMATION IN DOUBLE‐STRANDED DNA UPON NANOSECOND LASER‐INDUCED PHOTOIONIZATION

Abstract: Double-stranded (ds) calf thymus DNA (0.4 mM), excited by 20 ns laser pulses at 248 nm, was studied in deoxygenated aqueous solution at room temperature and pH 6.7 in the presence of a sodium salt (10 mM). The quantum yields for the formation of hydrated electrons (phi c-), single-strand breaks (phi ssb) and double-strand breaks (phi dsb) were determined for various laser pulse intensities (IL). phi c- and phi ssb increase linearly with increasing IL; however, phi ssb has a tendency to reach saturation at high… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
36
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(39 citation statements)
references
References 45 publications
3
36
0
Order By: Relevance
“…These radicals should then lead to ssb. Other experiments, however, contradict this hypothesis Bothe et al, 1990) since addition of t-butanol as a scavenger of OH radicals does not lead to a smaller yield of strand breakage in deoxygenated solutions (Table 4). Control experiments in the presence of N 2 0 showed that @ssb is significantly larger than under argon since OH radicals, which are formed by reaction of e& with N20, contribute to strand breakage (see Section 5).…”
Section: Other Polynucleotidesmentioning
confidence: 77%
See 2 more Smart Citations
“…These radicals should then lead to ssb. Other experiments, however, contradict this hypothesis Bothe et al, 1990) since addition of t-butanol as a scavenger of OH radicals does not lead to a smaller yield of strand breakage in deoxygenated solutions (Table 4). Control experiments in the presence of N 2 0 showed that @ssb is significantly larger than under argon since OH radicals, which are formed by reaction of e& with N20, contribute to strand breakage (see Section 5).…”
Section: Other Polynucleotidesmentioning
confidence: 77%
“…This transfer mechanism is essentially based on ps excitation measurements of thymine . For ns excitation of polynucleotides and DNA using much lower pulse intensities, this mechanism could not be substantiated Bothe et al, 1990). It should be noted that eLq does not lead to ssb, e.g.…”
Section: Photoionizationmentioning
confidence: 96%
See 1 more Smart Citation
“…Unlabeled ethanol (chemical purity 99.5%), and three partially labeled forms of ethanol, CD 3 The chemical purities, and the absence of any partially labeled isotopomers, were confirmed via mass spectrometric analyses of these materials. The aryl radicals were generated and isolated, and their reactivities were then studied, as described previously [12,13].…”
Section: Methodsmentioning
confidence: 99%
“…This experimental method involves studying the reactivities and selectivities of derivatives of the radicals that contain a chemically inert, charged group (distonic ions), which allows them to be manipulated in a Fourier-transform ion cyclotron resonance (FT-ICR) mass spectrometer. A large number of studies suggest that the action of some potential anti-tumor antibiotics is based on H-atom abstraction by aromatic, ,-biradical intermediates from a sugar moiety in DNA (which ultimately leads to cell death) [1][2][3][4][5][6][7][8][9]. These compounds, however, are also destructive to healthy cells.…”
mentioning
confidence: 99%